2019
DOI: 10.3928/19404921-20190122-01
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Use Patterns Among Patients With Dementia During Transitions From Hospitals to Skilled Nursing Facilities

Abstract: Gaps in pain management, including discontinuity in analgesic medication prescribing, frequently complicate transitions from hospital-to-skilled nursing facilities (SNFs) for patients with dementia. The objective of the current study was to examine analgesic medication use and prescribing patterns in the last 48 hours of hospitalization and upon discharge to SNF among stroke and hip fracture patients with dementia. Of 318 patients that received an analgesic medication within the last 48 hours of hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The finding of a lower likelihood of opioid use for residents newly admitted to LTC (evident even among those with severe pain) raises concerns regarding possible discontinuity in the assessment, recognition, and/or treatment of pain among older adults during care transitions (e.g., from home to hospital to LTC). Gilmore-Bykovskyi et al [ 41 ] found that 23% of persons with dementia who were prescribed an analgesic in hospital experienced a potentially abrupt discontinuation when discharged to skilled nursing facilities. It is also possible that heightened concern and oversight of opioid prescribing in the community [ 25 ] is contributing to a reduced prevalence of opioid use among those entering LTC more recently [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a lower likelihood of opioid use for residents newly admitted to LTC (evident even among those with severe pain) raises concerns regarding possible discontinuity in the assessment, recognition, and/or treatment of pain among older adults during care transitions (e.g., from home to hospital to LTC). Gilmore-Bykovskyi et al [ 41 ] found that 23% of persons with dementia who were prescribed an analgesic in hospital experienced a potentially abrupt discontinuation when discharged to skilled nursing facilities. It is also possible that heightened concern and oversight of opioid prescribing in the community [ 25 ] is contributing to a reduced prevalence of opioid use among those entering LTC more recently [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that HHC patients with ADRD are less likely to use any analgesic for daily interfering pain is consistent with prior studies, which found that pain is undertreated in community-dwelling older adults with ADRD in general, 14 and even more so during post-acute care transitions. 4,5,12,[19][20][21] Multiple factors may have contributed to the undertreatment of pain in older persons with ADRD during post-acute care. 40 First, impaired cognition may limit the patient's ability to self-report pain and changes in pain since administration of analgesics, potentially leading to under-treatment of pain.…”
Section: F I G U R E 1 Mean Of Activity Of Daily Living Score Changes...mentioning
confidence: 99%
“…41,43 Finally, factors specific to post-acute care transitions, such as when one receives HHC after hospital discharge, may also have caused the undertreatment of pain in HHC patients with ADRD. In particular, documentation of pain during hospitalization is often fragmented, one time only, and with insufficient information on pain treatment (e.g., effects of analgesics), 40,41,44 and analgesics are not often prescribed on standing orders in the hospital discharge summary, 20 resulting in gaps in pain management in post-acute care. This is because postacute care providers often rely on the written hospital discharge summary to guide their plan and provision of care, 21 and most post-acute care settings such as skilled nursing facilities and HHC do not have ready access to prescribers even if pain is identified by HHC providers.…”
Section: F I G U R E 1 Mean Of Activity Of Daily Living Score Changes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Abstraction procedures were performed in a standardized manner using abstraction manuals and tools with training and guidance for medical record review based on prior work. 40,41 Guidance on identifying NPS within clinical documentation contained within abstraction manuals and tools was informed by the Neuropsychiatric Inventory. 42 Specific variables included anxiety, agitation/aggression, hallucinations, depression, disinhibition, irritability or lability, and aberrant motor behavior (Supplementary Material 1).…”
Section: Data Collection and Analysismentioning
confidence: 99%